Drought-tolerant cowpea - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The drought tolerance of some 900 different strains of cowpea was evaluated in a collaborative research programme betweenscientists from the Japan International Research Center for Agricultural Sciences (JIRCAS) and IITA. The scientists found...